2013
DOI: 10.1007/s00267-013-0120-y
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-scale Spatial Analysis of Native and Exotic Plant Species Richness Within a Mixed-Disturbance Oak Savanna Landscape

Abstract: Impacts of human land use pose an increasing threat to global biodiversity. Resource managers must respond rapidly to this threat by assessing existing natural areas and prioritizing conservation actions across multiple spatial scales. Plant species richness is a useful measure of biodiversity but typically can only be evaluated on small portions of a given landscape. Modeling relationships between spatial heterogeneity and species richness may allow conservation planners to make predictions of species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The relationship of native to exotic richness has often been observed to depend on spatial scale—both extent and grain [ 65 ]—with natives and exotics positively correlated at large scales and negatively correlated at smaller scales [ 66 70 ]. Davies et al [ 71 ] suggested this scale dependence was a result of spatial heterogeneity, a pattern strongly influenced by disturbance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship of native to exotic richness has often been observed to depend on spatial scale—both extent and grain [ 65 ]—with natives and exotics positively correlated at large scales and negatively correlated at smaller scales [ 66 70 ]. Davies et al [ 71 ] suggested this scale dependence was a result of spatial heterogeneity, a pattern strongly influenced by disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Where disturbance was high at either local or landscape scales, native species declined while exotic species richness increased ( Fig 3 ). Schetter et al [ 70 ] similarly found that richness of natives and exotics was best explained at different scales of land cover. A meta-analysis also showed that the impacts of exotics on species richness declined with the study’s spatial scale [ 74 ] and exotic species can also alter species area relationships [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study in GBNWR, for instance, we found that the density of T. sebifera decreased significantly with distance to road (the edge effect) and more T. sebifera trees were clumped underneath the range of an overstory slash pine tree's crown and around snags of high-decay classes in forest interiors (the snag effect) (Fan 2018). Other studies also report bird-mediated dispersal limitation and patchy distribution of invasive species at the landscape level (Bartuszevige et al 2006;Schetter et al 2013). Mechanistically, three key processes-seed dispersal, seed germination, and seedling recruitment (growth)are involved in T. sebifera spread in the landscape (Figure 2).…”
mentioning
confidence: 81%
“…These are examined through the lens of area, density, edge, shape, proximity, interspersion, connectivity and diversity metrics, which include parameters such as number of patches, perimeter-area ratio, patch richness, etc. (Torbick et al 2006;Driezen et al 2007;Schetter et al 2013;Herse et al 2018). These metrics, specifically landscape and class-level, are reliable for assessing natural and/or anthropogenic LULC changes that disrupt abiotic or biotic landscape structure including management activities (Gottgens et al 1998;Lopez et al 2002;Houlahan and Findlay 2004;Johnston and Rejmánková 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An example of one of these dynamic yet diverse landscapes is Oak Openings Region within southeastern Michigan and northwestern Ohio, USA, described in more detail below. Large conservation efforts have focused on examining the changes within this region (e.g., Schetter et al 2013 ; Abella et al 2017 ), and there have been significant alterations as a result of anthropogenic activities (e.g., development, restoration), natural disturbance (e.g., tornado) and invasive species (e.g., emerald ash borer, Agrillus planipennis , Fairmaire). Traditional approaches towards ecological restoration include the community and ecosystem approach.…”
Section: Introductionmentioning
confidence: 99%